Peranan Ikatan Mahasiswa Kecamatan Batang Kuis Dalam Meningkatkan Kualitas Pendidikan Masyarakat Di Kecamatan Batang Kuis - Muhammad Zuhri (Pusdikra Publishing, 2021)
The purpose of this study was to reveal the role of students as agents of change in improving the quality of education in the Batang Kuis sub-district. This study used qualitative methods, observations and interviews as techniques in data collection in this study. The results of this study are that students are agents who have more thoughts to lead to changes that are beneficial to the surrounding community in many ways. As stated in the Tri Dharma of Higher Education which explains about education and teaching which is something that students do, namely studying on campus and off campus and being able to implement the knowledge they have acquired to many people. Second, regarding research and development, subordinate students have an obligation to be able to research any problems that occur in the community, especially in the field of education, so that when students understand the problems that occur in society, students must develop community resources and the potential of the students themselves to implemented for the general public. Finally, community service is that students must be able to provide a positive side such as providing socialization to the community about something new and students can be a mouthpiece for community aspirations.